INSIDENSI PENYAKIT LAYU BAKTERI PADA TANAMAN KENTANG (Solanum tuberosum L) DI KECAMATAN MODOINDING - Monica Wenas; Guntur S.J. Manengkey; Henny V.G. Makal (Universitas Sam Ratulangi, 2016)
ABSTRACTThis reseach aims study the wilt desease of bacterial on potato held in Mondoinding District for3 monts from January to April 2016. Laboratory studies conducted at the Laboratory ofMicrobiology and Plant Pathology, Faculty of Agriculture Unsrat Manado and in the field whichis in Modoinding District. The research in the laboratory is to determine the pathogenic bacteriathe causes wilt disease while in the field is to determine the incidence of the disease thet carriedout in the Linelean village, Makaaroyen village and Palelon village using subplots extent of 2 mx2 m and the spacing used between the plants is 40 cm x 20 cm with the number of samples ineach subplot at 22 plants, to study the incidence of the disease by the method of survey andsampling deliberate on potato experiencing symptoms of wilting. The result showed that thecharacteristic of pathogenic bacterial causing wilt disease on potatoin the Modoinding Districtthat Ralstonia solanacearum, is the symptoms of the plants become wither, the stem becomesbrown and rotten. The result of the study the incidence of wilt diseases caused by pathogenicbacteria in the field have differences with the incidence of wilt diseases caused by pathogenicbacteria at each location, with the highest incidence is Linelean village with 51.58%, followed by44.88% Palelon village and the Makaaroyen village 40.78%. The incidence of bacterial wiltdisease in Modoinding district each location of the observations is increasing every week withthe highest incidence of will disease caused by pathogenic bacteria is an average of 78.62% andthe lowest attack which is an average of 5.45%.